Effect of Hydrolyzed Lima Protein (Phaseolus Lunatus) on The Quality of Yogurt Products - Pham, Thi Hoan; Phan, Ngoc Thuy Tien; Duong, Tran Minh Tran (Journal of Technical Education Science, 2023)
This study was conducted to evaluate the quality of yogurt with partial replacement of hydrolyzed Lima protein (Phaseolus lunatus). The hydrolysis of phaseolus protein by Alcalase at the rate of 0.24 AU/g protein, at 50 °C, shaking speed of 150 rpm for 1 hour was used to receive the hydrolyzed protein. The analytical results showed that the hydrolyzed protein content had a great influence on the whey separation of yogurt. The higher the hydrolyzed protein content (0% - 2%), the higher the whey separation (39.12% - 46.6%). Besides, hydrolyzed protein also contributed to shortening yogurt fermentation duration. The results of rheological analysis of yogurt samples showed that the yogurts partially replaced with hydrolyzed Lima protein had higher viscosity and shear stress than the reference sample 1 (Ref1 - without protein replacement). Sensory evaluation results showed that yogurt samples replacing 1% hydrolyzed protein (YP1) were preferred over other replacement samples. Microbial transglutaminase (MTGase) of 1.5 IU/g protein formed a cross-link between protein molecules that improved the water holding capacity of yogurt better than the Ref1. Product YP1 has chemical composition and microbiological criteria that meet the standards of TCVN 7030:2009 (Codex stan 243-2003) about fermented milk. The technological process of the researched yogurt production is fully applicable at pilot and industrial scales.